Effect of different nickel-titanium rotary files on dentinal crack formation during retreatment procedure - Mehmet Çitak; Taha Özyürek (Tabriz University of Medical Sciences, 2017)
Background. The aim of this study was to compare the dentinal defects caused by Reciproc, TF Adaptive and ProTaper Next NiTi rotary file systems during the retreatment procedure. Methods. A total of 150 mandibular incisors with straight and single root canals were included in the present study. All the root canals were prepared up to an apical diameter 0.40 mm using stainless steel files. Thirty teeth were randomly stored as the negative control group. A total of 120 specimens were obturated with gutta-percha and AH Plus sealer using vertical compaction technique. Thirty specimens with root canal filling were randomly separated for the only-filled group. Then the teeth were randomly divided into 3 groups; Reciproc, TF Adaptive and ProTaper Next. The retreatment procedure was performed with these NiTi files. Then 150 specimens were cut perpendicular to tooth axis at 3-, 6-, and 9-mm distances from the apex, and examined to determine the presence of any cracks at ×25 under a stereomicroscope. Chi-squared test was used at 5% significance level. Results. All the tested NiTi file systems were found to cause significantly more dentinal defects compared to unprepared and only-filled groups (P<0.05). No statistically significant differences were found between the groups in terms of dentinal defects (P>0.05). No correlation was found between the slice levels and the dentinal defect distribution (P>0.05). Conclusion. Within the limitations of present study, all the tested NiTi file systems were found to cause significantly more dentinal defects compared to unprepared and only-filled groups.